The Acquisition of English Passive Voice: A Study of Error Patterns in EFL Learners - Novriyani; Nurnalisa (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
The study investigated the acquisition of English passive and error paterns in EFL learners. Grammar constitutes the framework through which sentences and phrases are systematically formed, drawing upon acquired linguistic knowledge and established syntactic rules. In this research, the researcher used descriptive qualitative research which investigated the acquisition of English passive and students’ difficulties in studying error patern in EFL Learners. The sample of study was students of English Education Department at Islamic Institute of Darul A’mal Lampung. There are 15 students as the participant in this research. To achieve the purpose of study, the researcher used questionnaire and test. The result showed that there are 11 students have problems in passive voice in simple present tense and there are 12 students have problems in simple past tense. There are some students face difficulties to determine passive voice in simple present tense and simple past tense. The students’ problems are having difficulty in changing identifying passive voice in multiple choice form, having difficulty in changing identifying passive voice in essay form, having difficulty memorizing, using, and identifying Verb-3 both regular and irregular forms, having difficulty in changing using TO BE (is, am, are) and auxiliary verbs (do, did, have, has, had), and having difficulty in adjusting verb according to the subject (both singular and plural) in passive form.